EXPLORING THE ENGLISH LANGUAGE NEEDS OF WAITRESSES AT BAMBOO CAFÉ, PENGLIPURAN VILLAGE - Ni Luh Eka Setyawati; Ni Putu Alia Anjani; Ni Nyoman Padmadewi (Lingua Scientia, 2026)
Penglipuran Village in Bali is one of the popular cultural destinations in Indonesia that attracts both local and foreign visitors. As a restaurant located in this tourism area, Bamboo Café serves customers from different countries, making English an important tool for daily communication. This study aimed to explore the English language needs of waitresses at Bamboo Café, Penglipuran Village. A descriptive qualitative design was used in this study. The participants were waitresses and the restaurant manager. Data were collected through semi-structured interviews, observations, and document analysis. The data were analyzed based on needs analysis framework focusing on necessities, lacks, and wants. The findings showed that waitresses used English when greeting guests, explaining food and beverage menus, taking orders, answering customer questions, and providing information related to Penglipuran Village. However, they still faced some difficulties when using English. Most participants had limited vocabulary related to food, beverages, and cultural information. Therefore, English learning materials for waitresses should focus on hospitality communication and restaurant service activities.